A Patient-Prioritized Agenda for Information Needs During the COVID-19 Pandemic: A Qualitative Study of Patients With Inflammatory Bowel Disease. Issue 4 (19th September 2021) - Long, Millie D; Grewe, Mary E; Cerciello, Emily; Weisbein, Laura; Catabay, Kyra; Kappelman, Michael D
Abstract: Background: Patients with inflammatory bowel disease (IBD) may be at risk for complications due to the COVID-19 pandemic. We performed a qualitative study to better understand IBD patient experiences and concerns when navigating the COVID-19 pandemic, with the goal of prioritizing patients' information needs. Methods: We conducted a series of semistructured virtual focus groups at 6 months, then member checking focus groups 1 year into the COVID-19 pandemic. We included questions on patients' experiences navigating the pandemic with IBD, differences in their experience as compared to peers, their concerns and fears, as well as preferred information sources. Transcribed focus groups were coded and content analyzed to summarize key areas of interest and identify themes. We focused on 4 areas in our content analysis process: fears, challenges, information preferences, and research questions. Results: A total of 26 IBD patient participants were included in the initial focus groups. Findings highlighted the many challenges faced by patients during the COVID-19 pandemic, ranging from access (bathrooms, medications, healthcare) to significant fears and concerns surrounding medications used for IBD worsening risks of COVID-19. Research questions of importance to patients centered on understanding risks for COVID-19 complications, particularly pertaining to medication utilization, with a shift over time toward understanding COVID-19 vaccination. In our member checking focus groups ( n = 8 participants), themes were reiterated, with a central focus of research questions pertaining to COVID-19 vaccination. Conclusions: Information needs for patients during the COVID-19 pandemic centered upon understanding disease-specific risks. Identified challenges and fears will inform future research agendas and communication with patients. Lay Summary: We used focus groups to understand the concerns of patients with inflammatory bowel disease (IBD) during the COVID-19 pandemic. Patients' fears were linked to medications. Patients' questions shifted from understanding the risks of IBD medications to understanding COVID-19 vaccination. Graphical Abstract: